In with the New and Out with the Old? Competition and Electoral Specialisation among Europe’s Radical Left. The cases of Portugal, Greece, and France - Gago Rivas, Victor; Escobar Mercado, Modesto (Política y Sociedad, 2026)
The European radical left is not a homogeneous ideological family. While in most European countries there is a single radical left party with parliamentary representation, in some country’s electoral competition between classical communist parties and new radical left parties is common, with both gaining sustained parliamentary representation. However, how voters behave accordingly has not been studied. This article therefore uses data from the ten rounds of the European Social Survey covering thirteen elections held between 2000 and 2020 in Portugal, Greece and France to study the nature of electoral competition between these formations, as well as voter profiles. Our study reaffirms realignment theories, finding that competition occurs on both socio-demographic and socio-cultural axes. We find that parties specialise in attracting their electorates, avoiding cross-pressures. Thus, the communists attract an older, less educated and more union-affiliated electorate, which is also more Eurosceptic, more critical of immigration and ideologically more left-wing.